Pengaruh Financing to Deposit Ratio dan Non Performing Financing terhadap Return on Assets (Studi Kasus Bank Syariah Mandiri) - Prita Humairoh; Faisal Rakhman (Jurnal Accounting Information System (AIMS), 2020)
This study analyzes the effect of Financing to Deposit Ratio (FDR) and Non Performing Financing (NPF) on Return on Assets (ROA) based on the 2014-2018 BSM(BSM) financial statements. This research uses a quantitative method with an associative approach and then processed withstatistical software.The data of this study are secondary data in the form of quarterly financial reports of BSM with a sample of quarterly financial reports of BSMfor the 2014-2018 periode which have been audited and published as accountability to the public and the Financial Services Authority.The results showed that there was no effect of FDR on ROA based on the results of the t test, where the value of tcount <ttable (1.123 <2.109), while the NPF had a significant and negative effect on ROA referring the results of t test where tcount> ttable (-2,362 <2,109). This means that the amount of financing originating from customer funds has no effect on changes in net income, while the amount of problematic financing has a significant and negative effect on net income obtained by BSM.While simultaneously there is a significant effect of FDR and NPF on ROA in BSM based on the results of the F test, where the value of Fcount> Ftable (11,394> 3.59).This means that simultaneously the amount of financing disbursed and the amount of financing that has problems has a significant effect on BSMprofitability.